Editorial Foreword IJSLS Volume 3 Number 1 - Irianto, Sulistyowati (UI Scholars Hub, 2023)
The debate surrounding the compulsory inclusion of customary law as a teaching subject in nearly all Indonesian law faculties has garnered considerable attention in socio-legal studies